Method for Rapid Labeling of Waste Sludge from a Food Factory with 15N-Glycine and Evaluation of N Use Using Komatsuna (Brassica rapa Var. perviridis) - Mizuho Miura-Ido; Yuzuri Iwamoto; Hiroi Kouya; Yoshihiko Takahashi; Amjad Hassan; Norikuni Ohtake; Hidetaka Hori; Takuji Ohyama (International Journal of Agronomy)
The waste sludge from food factories has rich nutrients and useful material for fertilizer or animal feed, but quick treatments and recycling of the waste sludge are difficult due to its higher water content. We have developed a rapid composting system to make sludge fertilizer using mix of waste sludge and shredded newspaper (Sludge Fertilizer Made by Paper Mixing Method, SF-PMM). The mixture was incubated in a box reactor, continuously aerated with warm air around 35°C, and changed to mature SF-PMM, in only two weeks. To search movement of N from the SF-PMM to plants, we developed a new method to label small amounts of SF-PMM with 15N-glycine. 50 L of wastewater from a food factory was incubated with 1 L of active sludge and 3 g of 15N-glycine (98 atom% 15N), and 175 g of labeled sludge was obtained in a day. This sludge was mixed with 25 g of newspaper chips, packed between two steel meshes, and placed at 20 cm depth in the reactor composting 200 kg of unlabeled sludge-paper mixture. Composting was restarted, and after about 7 days of reaction, 15N-labeled SF-PMM 7.03 atom% 15N was obtained. The surrounding unlabeled compost contained 4.0, 4.0, and 0.8% of N, P2O5, and K2O, respectively. C/N and pH were 10 and 7.4, respectively. Komatsuna (Brassica rapa var. perviridis) was cultivated in a pot with 50 and 100 mg N of SF-PMM, and healthy plants were obtained as in the Control experiments containing 50 mg N ammonium sulfate. No growth inhibition was observed in these experiments. Even in 100 mg SF-PMM, excellent growth of the roots was observed. About 56% of the N in the plant was shown to come from 15N-SF-PMM, and about 6% of the total15N in the 15N-SF-PMM was also shown to be incorporated into the plant.